PENGARUH PERSEPSI RISIKO, PERSEPSI KEMUDAHAAN DAN PERSEPSI MANFAAT TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE DI MASYARAKAT KECAMATAN UTAN KABUPATEN SUMBAWA - Tulyanti, Eka Rahmat; Salam, Abdul (Jurnal Nusa Manajemen, 2024)
This research aims to examine the influence of perceived risk, perceived convenience and perceived benefits on purchasing decisions at the Shopee Marketplace in the Utan District, Sumbawa Regency. The sampling technique used is purposive sampling, namely the population used is based on predetermined criteria to be used as a sample. The research sample consisted of 100 people from Utan District, Sumbawa Regency. The analytical tool used in this research is multiple linear regression. The results of this research show that the Risk Perception variable has a positive and significant effect on Purchasing Decisionsat the Shopee Marketplace, the Convenience Perception variable does not have a significant effect on Purchasing Decisions at the Shopee Marketplace and the Benefit Perception variable has a positive and significant effect on Purchasing Decisions at the Shopee Marketplace.